Gametophytic self-compatibility and its influence on the physical characteristics of plum fruit - Carvalho, Flávio Corrêa de; Inglês, Bruna Aparecida; Silveira, Daniel Mocelin; Silva, Clandio Medeiros da; Francisco, André Luiz Oliveira de (Scientia Agraria Paranaensis, 2022)
Gametophytic self-incompatibility can be one of the obstacles to achieving high yields in plum orchards. The objective of this work was to verify in the field the occurrence of gametophytic self-compatibility, and its influence on the physical characteristics of fruits in Japanese plum accessions.. The work was installed at the Research Pole of IDR-Paraná in Ponta Grossa-PR, in 2021, selecting six accesses belonging to the active Plum-GAB site. The experimental design was completely randomized (DIC) with a split plot (6 x 2), with the plot having six accessions and the subplot having two methods of pollination, induced self-pollination and free pollination, with five replications. For the variables related to the physical quality of the fruits, the DIC was delimited, with the six accessions as treatment and four replicates of five fruits. The variables observed for self-compatibility were the ercentagem of apparent and effective fruiting. For the physical quality of fruits, the total mass, seed and erc, vertical and horizontal diameter, volume, erc yield and seed/fruit mass ratio were evaluated. Free pollination was higher in the ercentagem of apparent and effective fruiting, and the genotypes PR-1013 and PR-1095 were the materials that presented the highest percentages for these variables, as well as for the physical quality of the fruits. The Japanese plum accessions evaluated were classified as self-incompatible, with free pollination as the best pollination method for the production and quality of fruits of this species.